The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15218/zjms.2015.0038
|View full text |Cite
|
Sign up to set email alerts
|

The relation between central corneal thickness and axial length in a sample of Erbil population

Abstract: IntroductionThe axial length (AL) of the eye is the distance between the anterior and posterior poles of the eye, 1 and it is typically defined as the distance from the anterior corneal surface to the anterior surface of the retina. 2,3 In vivo, it is measured either by ultrasonography or by partial coherence interferometry. The AL of the eye at birth is approximately 17 mm and reaches approximately 24 mm in adulthood. It is typically longer than 24 mm in myopes and shorter than 24 mm in hyperopes. Each one mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“… 25 , 32 , 33 According to these studies, there is a drop in the density of keratocytes, a reduction in inter-collagen fiber lengths, and denaturing of collagen fibers as a person advances in age with resultant alteration in CCT. 34 , 35 Studies conducted in Nigeria and Africa at large have borne this out in studies quite similar to ours in which the authors reported that aging was associated with corneal thinning. 15 , 25 , 36 , 37 Although our study did not reveal significant clinical profiles that are typical of patients developing POAG that can be used as early indicators for the disease, apart from the usual monitoring of IOP, it is clear that individuals who require evaluation and management of glaucoma can be identified more readily through the provision of screening services and health education in communities, work, and religious institutions 38 so that patients at risk of glaucoma can be identified early and treated to avoid late presentation to the eye clinic with glaucoma and its associated complications.…”
Section: Discussionsupporting
confidence: 69%
“… 25 , 32 , 33 According to these studies, there is a drop in the density of keratocytes, a reduction in inter-collagen fiber lengths, and denaturing of collagen fibers as a person advances in age with resultant alteration in CCT. 34 , 35 Studies conducted in Nigeria and Africa at large have borne this out in studies quite similar to ours in which the authors reported that aging was associated with corneal thinning. 15 , 25 , 36 , 37 Although our study did not reveal significant clinical profiles that are typical of patients developing POAG that can be used as early indicators for the disease, apart from the usual monitoring of IOP, it is clear that individuals who require evaluation and management of glaucoma can be identified more readily through the provision of screening services and health education in communities, work, and religious institutions 38 so that patients at risk of glaucoma can be identified early and treated to avoid late presentation to the eye clinic with glaucoma and its associated complications.…”
Section: Discussionsupporting
confidence: 69%